Clinical misdiagnosis of influenza infection with a confusing clinical course: A case report - Arefeh Babazadeh; Zeinab Mohseni Afshar; Mohammad Barary; Rezvan Hosseinzadeh; Soheil Ebrahimpour (Clinical Case Reports, 2023)
Abstract A 32‐year‐old woman with a history of hypothyroidism and major depressive disorder was admitted with severe weakness and somnolence. She had tachycardia and hypotension, indicative of severe dehydration, and was treated with a vasopressor and sodium bicarbonate, but her clinical manifestations deteriorated. A high‐resolution computed tomography (HRCT) scan showed a patchy ground glass appearance with interlobular septal thickening, suggesting pneumonia. Reverse transcription‐polymerase chain reaction (RT‐PCR) was requested for the influenza A virus (IAV), which was positive. The patient was treated with oseltamivir and discharged with improved clinical symptoms.